Factores psicológicos asociados al juego problemático en estudiantes universitarios de Lima - Valdez Huarcaya, Nancy Eufemia (2023)
The aim of the study was to analyze the psychological variables that predict problem gambling in 173 engineering students, men and women, from the first years of study at a private university in Lima, Perú. The age range was 16 to 23 years (M = 17.9, SD = 1.2).The measures were the Personality Inventory NEO FFI (NEO Five-Factor Inventory, Costa & McCrae, 1992), the Academic Stress Inventory (SISCO, Barraza, 2007a), the Time Management Behavior Questionnaire (TMBQ, Macan, 1994) version translated into Spanish by García-Ros and Pérez-González (2012), and the South Oaks Gambling Screen, Revised for Adolescents (SOGS-RA, Becoña, 1997). The results indicated that the management of free time is a moderate predictor of problem gambling (standardized coefficient = -.33), followed by the agreeableness personality´s factor (standardized coefficient = -.29), while academic stress showed lower predictive capacity (standardized coefficient = .10). The results are discussed in relation to possible ways to prevent problem gambling.